A comparison of balloon-assisted versus dilator in percutaneous gastrostomy tube placement - Lee,Sean; Ghosh,Abheek; Raymond,Aislynn; Akhter,Nabeel M. (Journal of Clinical Imaging Science)
Objectives: This study assesses the safety and efficacy of balloon-assisted gastrostomy (BAG) compared to conventional techniques using dilators. Material and Methods: A single-center retrospective review of all fluoroscopically-guided percutaneous gastrostomy tube insertions from July 2017 to September 2020 was performed. Two hundred and seventy-three patients were included in this study, with 183 patients and 90 patients in the BAG and dilator groups, respectively. Fluoroscopy time, peak radiation dose, pain management, days to interventional radiology (IR) reconsultation, and post-operative complications (major and minor) for each procedure were reviewed to evaluate for statistical differences. Results: There were shorter fluoroscopy times (5.13 min vs. 7.05 min, P = 0.059) and a significantly lower radiation use (Avg = 102.13 mGy vs. 146.98 mGy, P < 0.05) in the BAG group. The BAG group required significantly lower operating time (41 min vs. 48 min, P < 0.01) and received lower pain management (fentanyl 75 mcg and midazolam 1.5 mg, P < 0.001). The mean days to IR reconsultation for the BAG group was greater (29 days vs. 26 days, P = 0.38). The overall rate of minor complications (grades 1 and 2, according to the CIRSE classification system) was higher in the dilator group (39% vs. 35% in BAG group, P = 0.53). No major complications were reported in either group. Conclusion: BAG is a safe and efficient technique for percutaneous gastrostomy tube placement. BAG patients required significantly lesser radiation, OR time, post-operative pain management, and recorded lower postoperative complications compared to their counterparts in gastrostomies utilizing dilators.